Developing a High-Fidelity Simulation Program in a Nursing Educational Setting. Issue 3 (July 2018) - King, Marsha
Abstract : This change project was developed in response to the lack of a high-fidelity simulation program at a midwestern university in the United States. The use of clinical simulation as a teaching-and-learning strategy has significantly increased within nursing education. Unlike some colleges, this university had a dedicated simulation laboratory with two high-fidelity simulators; however, there was no clinical simulation program to use this equipment. The expensive simulation equipment sat unused because of the lack of funding for dedicated faculty, lack of a champion to implement, shortage of faculty time, minimal knowledge of the use of high-fidelity simulators, and a lack of curriculum integration. The purpose of the project was to create a simulation program, including faculty development and curriculum integration of simulation-based experiences. The framework of the program was based on the International Nurses Association of Clinical Simulation and Learning "Standards of Best Practice: Simulation." The high-fidelity simulation program grew from 0 simulation encounter per year to greater than 250 per year from the onset of the project. Faculty accepted high-fidelity simulation as a new teaching strategy and incorporated a minimum of at least one simulation-based experience within their courses. Simulation has been integrated successfully into the current curriculum. Students and faculty have positively evaluated simulation as an effective teaching/learning strategy. Each semester has seen an increase in the number of simulations, types of simulations, and acuity of simulations offered in clinical courses for students.